Wet Land Schistosoma GIS Database of Development - Xiang-Mo Xie; Tao Xiong; Feng-E Ni (2013 Fifth International Conference on Measuring Technology and Mechatronics Automation, 2013)
With the perfection of high-tech and software development, GIS (Geographic Information System. listed GIS), Global Positioning System Global Positioning System, listed GPS) and Remote sensing (Remote sensing, RS for short) in the field of preventive medicine for the corresponding application and development. By RS and GPS collection schistosoma related to the wet land breeding regional information and the crowd infected areas of information distribution activities, include that information in the same geographical space combined with geography, computer science and technology, such as Internet integration to achieve comprehensive analysis, a digital means to achieve reunification of the whole planet, and related phenomena of the economy and understanding of the space environment and the multi-resolution, 3D description to deal with wet land and social aspects of the problem, through the use of statistical and graphical analysis, GIS can form a multi-level map data for computer analysis. Various spatial distribution of data calibration, we can use VFP, VF, Oracle and other database development software, composite information, query and mathematical modeling, database building wet land schistosomiasis situation, Lo intelligence database, livestock database control database. Once established, GIS provides a dynamic, quantitative, visual spatial analysis system, can be used to plan and carry out monitoring and wet land schistosomiasis epidemic prevention programs.